Compendium of selected studies on international monetary and financial issues for the developing countries - United Nations Conference on Trade and Development (New York : United Nations, 1987)
The collection of papers contained in this volume is an effort to contribute to the process of reflection on monetary and related issues. Papers presented examines international monetary issues in 1985, exchange rates systems and balance of payments experience and growth prospects of developing countries as well as debt and liquidity reforms.
At head of title: United Nations Conference on Trade and Development, Geneva.
Cover title: International monetary and financial issues for the developing countries.
"United Nations publication sales no. E.87.II.D.3"--T.p. verso.
Includes bibliographical references.
usc 26/09/2018
Loans
Keywords: International finance; Finance; Developing countries